‘Dry’ electrochemistry: A non-invasive approach to the characterization of archaeological iron objects - Doménech Carbó, Antonio (2021)
A methodology for monitoring the corrosion state of archaeological iron objects using ‘dry’ open circuit potential (OCP) measurements is described. Application of this technique to a set of objects from La Bastida de les Alcusses archaeological site (Moixent, València, Spain), dating back to the 4th century BCE, reveals significant differences depending on the conservation state. The transient OCP responses (which last between a few seconds and 10–15 min) were superimposed with much shorter (less than one second) intense features.